Synthesis and activation of carbon nanospheres for adsorption of organic pollutants - Goh, Jun Ming. (2010)
In this project, NaOH activated carbon nanosphere is used to investigate the adsorption capabilities for organic pollutants. As the activated carbon has extremely high adsorption capability, it is widely used in the wastewater treatment process. In this project, carbon nanospheres (CNS) was synthesized from glucose via an environmentally friendly procedure and the adsorption capability is being optimized. Methylene Blue (MB) was used as a model organic pollutant to investigate the adsorption capability of the CNS. It has been shown that NaOH activated CNS exhibit the most impressive adsorption capability at pH 10. The adsorption test was extended to 3 other similar organic dyes which are positively charged in nature. Results showed that all 3 different dyes could be adsorbed on the activated CNS surface but they occur at different rates due to the size difference of the organic dyes. UV regeneration and chemical regeneration methods were used to recycle the spent activated CNS (SA-CNS). The UV lamp proved to be ineffective in removing MB molecules from the SA-CNS. The chemical regeneration test involved the use of Cobalt nitrate and oxone to reactivate SA-CNS. This experiment proved to be effective in degrading the MB molecules from the surface of the SA-CNS. The maximum amount of MB dye which could be adsorbed on CNS surface was also determined (0.24g/ gram of CNS).